Restoration of the Eyebrows by Hair Transplantation - Gho, Coen; Neumann, Martino (Facial Plastic Surgery, 2014)
Partial loss of the eyebrows can be the result of epilation, scars, and inflammatory diseases. Facial hair and eyebrows play a major role in our mimetic expression and interaction. Therefore, facial hair restoration of the eyebrows can improve the appearance and psychological well-being of patients. We report the use of partial longitudinal follicular unit transplantation (PLFUT) to restore eyebrows. A total of 10 patients (age between 18 and 59 years; mean, 39 years) have been treated with PLFUT to restore the eyebrows. The grafts were harvested from the occipital area of the scalp. Suitable grafts were impregnated with a preservative solution and implanted into the eyebrows areas. Hair growth in the donor area as well as the eyebrows was observed before treatment and at intervals of 1 week, 3 months, and 1 year after treatment. Evaluation of the donor area reveals no visible scars with almost all hair follicles in the donor site reproducing hairs after 1 year. All treated patients were satisfied or very satisfied with their cosmetic results. PLFUT is a reliable, patient friendly method suitable for hair restoration of eyebrows in healthy persons as well as in burn scar tissue.
Keywords: hair; eyebrows; restoration; transplantation